2015
DOI: 10.2220/biomedres.36.195
|View full text |Cite
|
Sign up to set email alerts
|

<b>Three-dimensional reconstruction of serial sections for analysis of the microvasculature of the white pulp and the marginal zone in the human </b><b>spleen </b>

Abstract: Although a number of papers have given useful information on splenic microcirculation by light and/or scanning electron microscopy, controversies remain as to the vascular arrangement, especially in the human spleen. The present study re-examined the microvasculature of the human spleen using a three-dimensional reconstruction of immunohistochemically stained tissue sections, and showed that the central artery does not directly issue follicular arteries in the human spleen; follicular arteries are derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
2
16
2
2
Order By: Relevance
“…2.10), but no CD34-positive capillary endothelial cells inside the follicles. This corresponds to the results of others [Kusumi et al, 2015]. The histological reason for this fact needs to be investigated in more detail.…”
Section: Specimenssupporting
confidence: 87%
See 2 more Smart Citations
“…2.10), but no CD34-positive capillary endothelial cells inside the follicles. This corresponds to the results of others [Kusumi et al, 2015]. The histological reason for this fact needs to be investigated in more detail.…”
Section: Specimenssupporting
confidence: 87%
“…We reconstructed the capillaries inside and outside the follicles. Before our efforts (Chapter 7), only one study existed on this topic [Kusumi et al, 2015]. Fig.…”
Section: 'Follicle-double' and 'Follicle-single'mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another area of controversy concerning the blood supply of the white pulp has been recently addressed by 3D reconstruction studies. Kusumi et al [11] showed that different from what was suggested by previous evidence, the central arteries do not directly contribute to the vascularization of the white pulp. The white pulp is, instead, irrorated by harpin loop arterioles emerging from the penicillary artery; after that, it leaves the follicle or the lymphoid sheath surrounding the central artery.…”
Section: Spleen Microanatomy: the Pharmacologist Point Of Viewmentioning
confidence: 85%
“…Because of their anatomical location at the border of the red pulp, they have a rich supply of capillaries that are widely open. 4 MZ-B cells are thought to play an important role in rapid immune responses against bloodborne pathogens. In particular, they are believed to respond rapidly to polysaccharide antigens (TI-2 antigens), which are present on the surface of encapsulated bacteria such as pneumococci and meningococci.…”
Section: Introductionmentioning
confidence: 99%